2017
DOI: 10.1016/j.amjmed.2016.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Lack of Diagnostic Colonoscopy After Positive Result on Fecal Immunochemical Test in a Safety-Net Health System

Abstract: Background Effective colorectal cancer screening depends on timely diagnostic evaluation in patients with abnormal fecal immunochemical tests (FIT). Although prior studies suggest low rates of follow-up colonoscopy, there is little information among patients in safety-net health systems and few data characterizing reasons for low follow-up rates. Aims Characterize factors contributing to lack of follow-up colonoscopy in a racially diverse and socioeconomically disadvantaged cohort of patients with abnormal F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
107
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 26 publications
8
107
0
Order By: Relevance
“…The authors reported that 89% of patients with an abnormal FIT result were referred for follow‐up colonoscopy within 6 months, but only 44% actually underwent diagnostic colonoscopy. This level of follow‐up is consistent with the poor CDE rates reported in cited Veterans Administration, safety net, and other FQHC‐based studies …”
supporting
confidence: 86%
“…The authors reported that 89% of patients with an abnormal FIT result were referred for follow‐up colonoscopy within 6 months, but only 44% actually underwent diagnostic colonoscopy. This level of follow‐up is consistent with the poor CDE rates reported in cited Veterans Administration, safety net, and other FQHC‐based studies …”
supporting
confidence: 86%
“…Colonoscopy follow-up is complex because it involves the interaction of several levels of care and evaluating the appropriateness of an invasive diagnostic test (16, 17). Several patient-, provider-, and system-level factors have been evaluated to improve follow-up of test-positive patients (13, 1821), but lack of comparative data impedes implementation of potentially effective interventions.…”
mentioning
confidence: 99%
“…The interventions were effective for short-term but not long-term, follow-up. Several studies have described interventions aimed at increasing follow-up rates and showed mixed results [13,19,[27][28][29][30][31][32][33][34][35][36][37][38][39][40]. When the patient and physician's relations are good and based on clear communication and trust, the patient will be more likely to adhere to and fulfill the physicians' instructions [41,42].…”
Section: Repeated Automated Mobile Text Reminders For Follow-up Of Pomentioning
confidence: 99%
“…Barriers to follow-up after a positive FOBT have been identified in the literature [17][18][19][20][21][22] and are divided into four general groups based on whether they are related to patients, physicians, providers, or information technology [23][24][25]. Intervention programs have been developed to target each of these groups [26].…”
Section: Repeated Automated Mobile Text Reminders For Follow-up Of Pomentioning
confidence: 99%